Why humans like to cry tragedy, evolution and the brain - Trimble, Michael R. (Oxford, England Oxford University Press, 2012)
Humans are unique in shedding tears of sorrow. We do not just cry over our own problems: we seek out sad stories, go to film and the theatre to see Tragedies, and weep in response to music. What led humans to develop such a powerful social signal as tears, and to cultivate great forms of art which have the capacity to arouse us emotionally? Friedrich Nietzsche argued that Dionysian drives and music were essential to the development of Tragedy. Here, the neuropsychiatrist Michael Trimble, using insights from modern neuroscience and evolutionary biology, attempts to understand this fascinating and unique aspect of human nature--Book jacket.
Introduction -- Crying -- The neuroanatomy and neurophysiology of crying -- Evolution -- Tragedy and tears -- Tearful logic -- Why do we get pleasure from crying at the theatre? -- Appendices: Neuroanatomy -- Glossary of terms
Includes bibliographical references (pages 174-212) and index.
Keywords: Crying; Crying -- Physiological aspects; Tragedy